Vertical changes of the Co and Mn speciation along a lateritic regolith developed on peridotites (New Caledonia). (15th November 2017) - Dublet, Gabrielle; Juillot, Farid; Brest, Jessica; Noël, Vincent; Fritsch, Emmanuel; Proux, Olivier; Olivi, Luca; Ploquin, Florian; Morin, Guillaume
Abstract: Because they can host significant amounts of Co, the Mn-oxides are commonly considered as the major Co-bearing mineral species in lateritic environments. However, little is known about the process leading to the formation and/or the weathering of these Co-rich Mn-oxides. This lack of knowledge is mainly due to the fact that Co concentrations are too low in primary silicates for classical speciation analysis. In this study, we investigated both Co and Mn speciation in a 64 m thick lateritic regolith developed upon peridotites in New Caledonia, by combining High Energy Resolution Fluorescence Detection X-ray absorption Near Edge Structure (HERFD-XANES) spectroscopy at the Co K-edge with classical XANES spectroscopy at the Mn K-edge, bulk chemistry (ICP) and mineralogy (XRD). The results obtained provide new insights into the evolution of Co and Mn speciation as a function of the weathering stages. Co and Mn primarily occur as Co(II) and Mn(II, III) in olivine and serpentine in the bedrock. During the first weathering stage, these forms of Co and Mn are progressively oxidized toward Co(III) and Mn(III, IV), which occur mainly as Co(III)-bearing Mn(III/IV)-oxides in the transition between the saprolite and the laterite. In the uppermost lateritic horizons, long-time weathering resulted in a strong leaching of Co and Mn, and the remaining of these elements occurs as Co(II) and Mn(III) substituting for Fe(III) in goethite. This latter scavenging process emphasizes the importance of Fe-oxides for the long-term stabilization of Co and Mn in such deeply weathered laterites.